SAT0169 HYDROXYCHLOROQUINE PRESCRIPTION PATTERNS IN EUROPE - THE EUROPEAN SURVEY FOR LUPUS PATIENTS (ESLP). (2nd June 2020) - Osmani, Z.; Cornet, A.; Zacouris-Verweij, W.; Frankel, S.
Abstract : Background: Long-term use of hydroxychloroquine (HCQ) is very common in patients with lupus erythematosus. It has been associated with wide-ranging benefits and it is generally well tolerated 1 . However, long-term use (i.e. > 5 years) and high-dose HCQ (i.e. > 5 mg/kg/day) are both considered to be risk factors for developing HCQ retinopathy 2 . Advances in our understanding of HCQ retinopathy has led to changes in the recommendations for HCQ dosing and retinopathy screening 1-3 . The latest EULAR guidelines for the management of systemic lupus erythematosus (SLE) 4 recommend a maximum HCQ dose of 5 mg/kg/day and ophthalmological screening at baseline and annually after 5 years of HCQ treatment. Objectives: To assess whether recent EULAR guidelines regarding HCQ dosing and retinopathy screening are affecting prescription patterns and screening frequencies in Europe. Methods: Patients in Europe were given the opportunity to complete the online European Survey for Lupus Patients (ESLP) initiated by LUPUS EUROPE. The survey was promoted on social media from the 26 th of June – 11 th of July 2019. The survey consisted of 29 questions. Each participant was asked, among other things, to report their body weight (kg), daily HCQ dose and if they have received baseline screening and/or regular eye examinations. Results: The online survey was completed by 2938 lupus patients from 36 countries. The majority were female (86.5%) and diagnosed with SLE (85.7%). The daily HCQ dose (mg/kg) was available from 1678 patients (57.1%). The median ± IQR HCQ dose was 4.3 ± 2.5 mg/kg/day with a median treatment duration of 7 years (IQR: 3 – 14). The recommended daily HCQ dose of 5 mg/kg was exceeded by 618 patients (36.8%). Low HCQ dose (≤ 4 mg/kg) was reported by 769 patients (45.8%). In addition, 284 out of 1786 patients (15.9%) reported they skipped HCQ once a week or more often. Nevertheless, only 8.7% of patients reported that they were more likely to skip HCQ than other medication. Patients from Belgium, Israel, France and Portugal reported the highest HCQ dosages. In contrast, patients from Spain reported the lowest HCQ dosages (Figure 1 ). Moreover, 935 out of 1137 patients diagnosed in the past 10 years (82.2%) reported that they have received an ophthalmological screening at baseline. Lastly, 1167 patients reported long-term use of HCQ (i.e. ≥ 5 years). Only about 64% of them (n=748) reported that they receive regular eye examinations (i.e. at least once every year). Conclusion: Studies have suggested that prescription patterns in the USA and UK were already affected by guidelines regarding HCQ dosing 1 . We show large inter- and intra-country variations of HCQ dosing in Europe. Additionally, most centers fail to follow recent recommendations 4 regarding annual screening of retinopathy in case of long-term HCQ use. More research is needed to assess the clinical efficacy of low-dose HCQ and to confirm whether proper screening modalities are being employed as recommended by recent guidelines 2-4 . References: [1]Jorge A et al. Hydroxychloroquine retinopathy - implications of research advances for rheumatology care. Nat Rev Rheumatol. 2018 Dec; 14(12): 693-703. [2]Michael F. Marmor et al, 2016, Recommendations on Screening for Chloroquine and Hydroxychloroquine Retinopathy (2016 Revision). Ophthalmology. 123(6): 1386-94. [3]Imran H. Yusuf et al. The Royal College of Ophthalmologists recommendations on screening for hydroxychloroquine and chloroquine users in the United Kingdom: executive summary. Eye (Lond). 2018 Jul; 32(7): 1168–1173. [4]Fanouriakis A et al. 2019 update of the EULAR recommendations for the management of systemic lupus erythematosus. Ann Rheum Dis. 2019 Jun; 78(6): 736-745. Disclosure of Interests: None declared